Связь аллозимной изменчивости и фактической семенной продуктивности у пихты белой (Abies alba Mill.) из Украинских Карпат - Морозова, Н.Н.; Пирко, Я.В. (Промышленная ботаника, 2003)
Genetic peculiarities of the groups of Abies alba Mill. trees with the different actual seed productivity were studied. No pronounced interrelation between the number of full-sized seeds and some genetic indices was noted. When comparing the studied groups of trees there were no valid differences in the values of the observed and expected heterozygosity. Though the differences in the observed heterozygosity were 22,6% for the most representative (with a high and medium actual seed production) samples, a 15,6% surplus of heterozygous genotypes was indicated in the group of trees with a high seed productivity, the deficiency of heterozygotus genotypes being characteristic of the trees groups with the average seed production. Plants with a low and a very low productivity had the least amount of polymorphic loci (19,0 % and 28,6 %) and were reported to have the least allele and genotypic diversity.